Mechanistic organometallic chemistry - Brown, S; Brown, Stephen Laurence (1986)
﻿ A number of organometallic transformations related to proposed elementary steps in the reductive polymerization of carbon monoxide are discussed. The use of isonitrile as model ligands for carbon monoxide, with which they are isoelectronic, is proposed. Investigations show that alkyl migration to isonitrile is preferred over migration to carbon monoxide. Iminoformyl products due to hydride migration to isonitrile are not,,however, observed. Syntheses of a range of cationic complexes of the type [ (η5-C5H5)M(L)2(CNR)]+, [(η5-C9H7)Ru(L)2(CNR)]+ and [(η5-C9H7)M(L)2(CO)]+ (M = Fe, Ru; L = CO, phosphine) are described. In two cases, addition of hydride to the isonitrile cations is followed by protonation on work-up to give aminocarbene complexes. These are inert to further reduction under the conditions employed. The majority of isonitrile cations lose the isonitrile ligand to give good yields of metal hydride complexes. A mechanism involving ring-slippage of the hydrocarbon ligand is implicated. Hydride addition to η5-C9H7 complexes results, in the majority of cases, in loss of the hydrocarbon ligand from the complex and recovery of indane. Evidence for the intermediacy of metal formyl complexes in a number of hydride donation reactions is presented. These formyl complexes are formed from carbonyl hydride complexes either under moderate CO pressure or in THF solution. Hydride complexes lacking a carbonyl ligand are found to be inert. Finally, two reactions, one involving an alkyl migration reaction catalyzed by silver(I) salts, and the other involving the reduction of a metal acyl ligand to metal alkyl, are combined to demonstrate a model for carbon chain growth at a metal centre. The synthesis of an iron pentanoyl complex, followed by a decomplexation reaction, gives pentanoic acid in which all the catbon atoms are potentially directly derived from carbon monoxide. This is the first synthesis of a single homologous acid from carbon monoxide.